Intrapuparial stage aging and PMI estimation based on the developmental transcriptomes of forensically important Aldrichina grahami (Diptera: Calliphoridae) gene expression - Zhiyun Pi; Jingjing Huang; Shiwen Wang; Hui Xie; Yihong Qu; Ziqi Zhou; Shujuan Wang; Yishu Liu; Chudong Wang; Fanming Meng; Jifeng Cai (Heliyon, 2024)
Background: The expression profiles of differentially expressed genes (DEGs) during pupal development have been demonstrated to be vital in age estimation of forensic entomological study. Here, using forensically important Aldrichina grahami (Diptera: Calliphoridae), we aimed to explore the potential of intrapuparial stage aging and postmortem interval (PMI) estimation based on characterization of successive developmental transcriptomes and gene expression patterns. Methods: We collected A. grahami pupae at 11 successive intrapuparial stages at 20 °C and used the RNA-seq technique to build the transcriptome profiles of their intrapuparial stages. The DEGs were identified during the different intrapuparial stages using comparative transcriptome analysis. The selected marker DEGs were classified and clustered for intrapuparial stage aging and PMI estimation and then further verified for transcriptome data validation. Ultimately, we categorized the overall gene expression levels as the dependent variable and the age of intrapuparial A. grahami as the independent variable to conduct nonlinear regression analysis. Results: We redefined the intrapuparial stages of A. grahami into five key successive substages (I, II, III, IV, and V), based on the overall gene expression patterns during pupal development. We screened 99 specific time-dependent expressed genes (stage-specific DEGs) to determine the different intrapuparial stages based on comparison of the gene expression levels during the 11 developmental intrapuparial stages of A. grahami. We observed that 55 DEGs showed persistent upregulation during the development of intrapuparial A. grahami. We then selected four DEGs (act79b, act88f, up and ninac) which presented consistent upregulation using RT-qPCR (quantitative real-time PCR) analysis, along with consideration of the maximum fold changes during the pupal development. We conducted nonlinear regression analysis to simulate the calculations of the relationships between the expression levels of the four selected DEGs and the developmental time of intrapuparial A. grahami and constructed fitting curves. The curves demonstrated that act79b and ninac showed continuous relatively increasing levels. Conclusions: This study redefined the intrapuparial stages of A. grahami based on expression profiles of developmental transcriptomes for the first time. The stage-specific DEGs and those with consistent tendencies of expression were found to have potential in age estimation of intrapuparial A. grahami and could be supplementary to a more accurate prediction of PMI.